2003
DOI: 10.1177/070674370304800406
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Associated with Nonprescription Drug Use in Intentional Overdose

Abstract: Suicide-prone patients with a diagnosis of substance abuse and who possess prescription medications are unlikely to use OTC medications in overdose. For this cohort, this represents a relatively small proportion of patients whom clinicians should consider to be at greater risk for attempting suicide when using OTC medication, especially acetaminophen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
14
2
Order By: Relevance
“…As expected, patients who reported that they intended to kill themselves considered their overdose potentially more lethal than patients who denied suicidal intent, but this does not correlate with the real potential lethality as assessed by Clinical Toxicologists. Whereas it is commonly believed that men make more serious attempts than women and older people more than younger people, [6][7][8] we found no evidence to support this. Similarly, contrary to previous studies that suggested that prescription medications are considered more dangerous in overdose by the lay public, 10 our results indicate that patients tend to perceive as being equally lethal both prescription medications and substances that they buy over the counter.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…As expected, patients who reported that they intended to kill themselves considered their overdose potentially more lethal than patients who denied suicidal intent, but this does not correlate with the real potential lethality as assessed by Clinical Toxicologists. Whereas it is commonly believed that men make more serious attempts than women and older people more than younger people, [6][7][8] we found no evidence to support this. Similarly, contrary to previous studies that suggested that prescription medications are considered more dangerous in overdose by the lay public, 10 our results indicate that patients tend to perceive as being equally lethal both prescription medications and substances that they buy over the counter.…”
Section: Discussioncontrasting
confidence: 96%
“…The median Pierce SIS was 8.5/25 (IQR [4][5][6][7][8][9][10][11][12] and the correlation between the patient VAS and Pierce SIS was strong (r = 0.73, P < 0.0001). The correlation between the toxicology VAS and Pierce SIS was r = 0.25 (P = 0.0004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 90% have a diagnosable psychiatric condition,3 8 most frequently depression,1 3 10 14–17 although substance use disorders, personality disorders, anxiety-related disorders, eating disorders and schizophrenia are also common 3 9 18 19. Alcohol has been estimated to be involved in 28–40% of cases 10 13 20. Despite being highly recommended, psychosocial assessment of self-poisoning patients occurs in only around half of cases 9 21…”
Section: Introductionmentioning
confidence: 99%